2017
DOI: 10.1016/j.media.2017.07.004
|View full text |Cite
|
Sign up to set email alerts
|

Designing image segmentation studies: Statistical power, sample size and reference standard quality

Abstract: HighlightsA sample size calculation for segmentation accuracy studies is derived.Parameters include accuracy difference, algorithm disagreement and a design factor.A formula is derived to account for errors in the study reference standard.A case study illustrates the application of the theory to a segmentation study design.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 33 publications
1
14
0
1
Order By: Relevance
“…Moreover, we believe that the results from this work may corroborate the findings of a number of previous studies in which caution has been raised over the interpretation of the value of some segmentation metrics, and the resulting league table positions in segmentation challenges ( Gibson et al., 2017a , Reinke et al., 2018 ). With evidence from the prostate segmentation in MRIs, we found that a statistically significant difference in the DSC between segmentations produced by two CNNs, does not necessarily lead to any detectable impact in other computational tasks within a clinical workflow that use these segmentations.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Moreover, we believe that the results from this work may corroborate the findings of a number of previous studies in which caution has been raised over the interpretation of the value of some segmentation metrics, and the resulting league table positions in segmentation challenges ( Gibson et al., 2017a , Reinke et al., 2018 ). With evidence from the prostate segmentation in MRIs, we found that a statistically significant difference in the DSC between segmentations produced by two CNNs, does not necessarily lead to any detectable impact in other computational tasks within a clinical workflow that use these segmentations.…”
Section: Discussionsupporting
confidence: 85%
“…Partly limited by the test data size of 30 images provided in the PROMISE12 Challenge, the diminishing statistically significant differences among top performing segmentation algorithms ( Gibson et al., 2017a ) can complicate interpreting these differences, if any, in segmentation accuracy. In other research fields, however, examples of networks that demonstrated statistical differences between different architectures include the introduction of residual networks ( He et al., 2016 ) and densely connected networks ( Huang et al., 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore the resection cavity should be clearly present on visual inspection. A total of 30 patients were retrospectively included in the study, which is in line with recommendations for the evaluation of segmentation accuracy from Gibson et al [25]. All patients received adjuvant concomitant chemo-radiotherapy with Temozolomide.…”
Section: Patientsmentioning
confidence: 99%
“…LeukNet was designed after analyzing the previously described results, where VGG-16 and VGG-19 architectures presented the best outcomes, with similar values for the mDFT approach in the ALL-IDB2 dataset. Therefore, we performed the Student's t-test [37] to statistically compare the results at a significance level of 5%. From the test performed, we found that the results were equivalent.…”
Section: A Models and Fine-tuning Evaluationmentioning
confidence: 99%